2009
DOI: 10.4172/1948-5956.1000003
|View full text |Cite
|
Sign up to set email alerts
|

Regrowth Concentration Zero (RC0) as Complementary Endpoint Parameter to Evaluate Compound Candidates During Preclinical Drug Development for Cancer Treatment

Abstract: The screening process for potential anticancer drugs involves expensive and time consuming preclinical and clinical trials (CT) before a drug is approved for clinical use (CU). At present, there is a "bottleneck" at the CT/CU transition because many drugs that showed promising results during preclinical research did not pass clinical trials. We speculated that the endpoint parameters (the inhibitory concentration 50 (IC 50 ) or lethal concentration 100 (CL 100 )) commonly used in proliferation assays for short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The anti-proliferative effect of menadione has been studied in several glioma cell lines and showed IC 50 values ranging between 13.5 μM to ~25 μM [1, 24] . We recently suggested that drug concentrations much higher than the IC 50 might be required to eliminate 100% of tumor cells and that the IC 50 is not the best parameter to evaluate anti-cancer drugs because it does not select for useful clinical drugs [14].
Fig.
…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The anti-proliferative effect of menadione has been studied in several glioma cell lines and showed IC 50 values ranging between 13.5 μM to ~25 μM [1, 24] . We recently suggested that drug concentrations much higher than the IC 50 might be required to eliminate 100% of tumor cells and that the IC 50 is not the best parameter to evaluate anti-cancer drugs because it does not select for useful clinical drugs [14].
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…Cells were routinely cultured as previously described [14]. Patients-derived glioblastoma cells hGCL1- hGCL8 were kindly provided by Dr Peter Siesjö (Lund University).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…also granulocyte-Macrophage Colony-Stimulating Factor, Interferon Alpha and Interleukin-2 as Adjuvant Treatment for High-Risk Renal Cell Carcinoma [47] similarlyPre-clinical Validation of Targeted Radionuclide Therapy Using a [ 131 I] Labelled Iodoquinoxaline Derivative for an Effective Melanoma Treatment [48]. Baculovirus expressed tumstatin was used to evaluate its anti-angiogenic and anti-tumarogenic functions such as inhibition of endothelial cell proliferation, cell viability, migration, tube formation, cap dependent protein translation and the associated signaling mechanism including in-vivo tumor study [49]. Regrowth Concentration Zero (RC0) as complementary endpoint parameter evaluates compound candidates during preclinical drug development for cancer treatment [50].…”
Section: Role Of P53 In Cancer Therapymentioning
confidence: 99%